Nivolumab Plus Cabozantinib With or Without Ipilimumab for Advanced Hepatocellular Carcinoma: Results From Cohort 6 of the CheckMate 040 Trial. Issue 9 (20th March 2023) - Yau, Thomas; Zagonel, Vittorina; Santoro, Armando; Acosta-Rivera, Mirelis; Choo, Su Pin; Matilla, Ana; He, Aiwu Ruth; Cubillo Gracian, Antonio; El-Khoueiry, Anthony B.; Sangro, Bruno; Eldawy, Tarek E.; Bruix, Jordi; et al.
Abstract : PURPOSE: To investigate the safety and efficacy of nivolumab plus cabozantinib with or without ipilimumab in patients with advanced hepatocellular carcinoma. METHODS: In cohort 6 of the multicohort, open-label, phase I/II CheckMate 040 study, patients who were treatment-naive, sorafenib-intolerant, or had progressed on sorafenib were randomly assigned 1:1 to nivolumab 240 mg once every 2 weeks plus cabozantinib 40 mg once daily (doublet arm); or nivolumab 3 mg/kg every 2 weeks plus cabozantinib 40 mg once daily with ipilimumab 1 mg/kg once every 6 weeks (triplet arm). Primary objectives were safety and tolerability, objective response rate, and duration of response by investigator assessment per RECIST v1.1. Secondary objectives included progression-free survival (by blinded independent central review) and overall survival. RESULTS: Seventy-one patients were randomly assigned: 36 to the doublet arm and 35 to the triplet arm. After 32.0-month median follow-up, objective response rate (95% CI) was 17% (6 to 33) and 29% (15 to 46) in the doublet and triplet arms, respectively. Median (95% CI) duration of response was 8.3 (6.9 to not estimable) months in the doublet arm and not reached (0.0 to not estimable) in the triplet arm. Median progression-free survival was 5.1 and 4.3 months, and median overall survival was 20.2 and 22.1 months for the doublet and triplet arms, respectively. Grade 3-4 treatment-related adverse events occurred in 50% and 74% of patients and treatment-related adverse events leading to discontinuation were reported for 11% and 23% in the doublet and triplet arms, respectively. There were no treatment-related deaths in either arm. CONCLUSION: Nivolumab plus cabozantinib with or without ipilimumab showed encouraging preliminary antitumor activity and had consistent safety profiles with those established for the individual drugs in patients with advanced hepatocellular carcinoma.